(untitled) (Physical Education, Health and Social Sciences, 2025)
Purpose: Organizational effectiveness and sustainability are increasingly linked to employee well-being and discretionary behaviors that go beyond formal job requirements. Quality of Work Life (QWL), reflects employees’ perceptions of a supportive and fulfilling work environment, plays a crucial role in fostering such positive behaviors. While prior studies have examined the direct effects of QWL on Organizational Citizenship Behavior (OCB), the psychological mechanisms underlying this relationship remain underexplored. This study aims to investigate job involvement (JI) as a mediating variable in the relationship between QWL and OCB, within the context of a public sector organization in Pakistan. Design: A cross-sectional survey was conducted using an online questionnaire distributed to employees of the Khyber Pakhtunkhwa Education Monitoring Authority (KPEMA), Pakistan. A total of 265 responses were collected from 14 districts across the province. Methods: To examine the mediating effect of job involvement between QWL and OCB, Hayes’ PROCESS Macro (Model 4) was applied using SPSS Version 20. However, AMOS 26 was used for confirmatory factor analysis. The model allowed for the assessment of both direct and indirect effects within the hypothesized framework. Findings: The results revealed a significant positive relationship between QWL and OCB. Moreover, job involvement significantly mediated this relationship, indicating that employees who perceive higher quality of work life are more likely to become psychologically engaged in their roles, which subsequently enhances their organizational citizenship behavior. Conclusions: The findings of the study underline that enhancing the QWL fosters greater JI. Moreover JI in turn promotes OCB. This chain of influence highlights JI as an important psychological mechanism through which QWL shapes positive discretionary behaviors in the workplace. Implications: The study provides valuable insight for public sector organizations. Specifically, those organizations who are seeking to enhance employee driven organizational performance. By prioritizing QWL initiatives like fair compensation, career growth, work life balance and safe work environment, managers can cultivate a more engaged workforce. Such workforce is more likely to exhibit higher levels of OCB. This can ultimately contribute to a more collaborative and productive work environment in an organization.